Preparation of chitosan/poly(Vinyl alcohol) nanocomposite films incorporated with oxidized carbon nano-onions (multi-layer fullerenes) for tissue-engineering applications (2019)
Recently, tissue engineering became a very important medical alternative in patients who need to regenerate damaged or lost tissues through the use of scaffolds that support cell adhesion and proliferation. Carbon nanomaterials (carbon nanotubes, fullerenes, multi-wall fullerenes, and graphene) became a very important alternative to reinforce the mechanical, thermal, and antimicrobial properties of several biopolymers. In this work, five different formulations of chitosan/poly(vinyl alcohol)/oxidized carbon nano-onions (CS/PVA/ox-CNO) were used to prepare biodegradable scaffolds with potential biomedical applications. Film characterization consisted of Fourier-transform infrared (FTIR) spectroscopy, thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), tension strength, Young’s modulus, X-ray diffraction spectroscopy (XRD), scanning electron microscopy (SEM), and energy-dispersive spectroscopy (EDS). The degradation in a simulated body fluid (FBS) demonstrated that all the formulations lost between 75% and 80% of their weight after 15 days of treatment, but the degradation decreased with the ox-CNO content. In vivo tests after 90 days of subdermal implantation of the nanocomposite films in Wistar rats’ tissue demonstrated good biocompatibility without allergenic reactions or pus formation. There was a good correlation between FBS hydrolytic degradation and degradation in vivo for all the samples, since the ox-CNO content increased the stability of the material. All these results indicate the potential of the CS/PVA/ox-CNO nanocomposite films in tissue engineering, especially for long-term applications.